Acculturation and Naturalization: Insights From Representative and Longitudinal Migration Studies in Germany - Maehler, Débora B.; Weinmann, Martin; Hanke, Katja (Frontiers in Psychology, 2019)
In recent years, Western countries have been experiencing a growing wave of immigration. Due to this development, these countries are facing great challenges in successfully integrating large numbers of immigrants and in preserving social cohesion. Research has already developed several assumptions about and models of how acculturation processes occur. The present contribution aims to investigate the relationship between the acculturation (and acculturation profiles) of immigrants and naturalization in their residence countries. Based on representative and longitudinal data, our investigation is a case study on Germany – one of the main receiving countries in recent years. Results show that acculturation in the country of residence is crucial for immigrants’ motivation to take up citizenship. Likewise naturalization leads to an increase in identification with the residence country.